2022
DOI: 10.1021/acs.organomet.2c00016
|View full text |Cite
|
Sign up to set email alerts
|

Ni-Catalyzed Larock Indenone Annulation with Aliphatic- and Silyl-Substituted Alkynes Supported by Mechanistic Analysis

Abstract: A Ni-catalyzed annulation reaction to synthesize indenones is reported. The reaction provides high yields and regioselectivities when aliphatic- and silyl-substituted alkynes are employed. Both have been challenging and underutilized substrate classes. Several mechanistic observations aided in the development of this reaction, including that β-hydride elimination is turnover-limiting for ortho-halogenated aldehyde substrates and that alkyne dissociation is rate-limiting for internal aliphatic alkynes. We antic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 75 publications
0
5
0
Order By: Relevance
“…In 2022, Wilger and coworkers reported a Ni‐catalyzed indenone synthesis that used methyl ortho ‐bromobenzoate esters as aromatic precursors ( 48 , Scheme 42). [16b] Initial studies with ortho ‐bromobenzaldehyde ( 6 ) indicated that alkyne dissociation was rate‐limiting under conditions with excess alkyne. Reaction byproduct analysis and KIE studies indicated that β‐hydride elimination was turnover‐limiting with benzaldehyde derivatives.…”
Section: Ni‐catalyzed Indenone Synthesismentioning
confidence: 99%
See 4 more Smart Citations
“…In 2022, Wilger and coworkers reported a Ni‐catalyzed indenone synthesis that used methyl ortho ‐bromobenzoate esters as aromatic precursors ( 48 , Scheme 42). [16b] Initial studies with ortho ‐bromobenzaldehyde ( 6 ) indicated that alkyne dissociation was rate‐limiting under conditions with excess alkyne. Reaction byproduct analysis and KIE studies indicated that β‐hydride elimination was turnover‐limiting with benzaldehyde derivatives.…”
Section: Ni‐catalyzed Indenone Synthesismentioning
confidence: 99%
“… Selected examples for Ni‐catalyzed indenone synthesis with methyl ortho ‐bromobenzoate esters and silyl‐substituted alkynes (Wilger, 2022) [16b] …”
Section: Ni‐catalyzed Indenone Synthesismentioning
confidence: 99%
See 3 more Smart Citations